Profile of Lymposites in New Tuberculosis (TB) Patients in Semarang City - Roni Afriansya; Nurul Qomariyah; Anung Sugihartono; Eko Naning Sofyanita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The body's form of defense or natural immune response against intracellular bacteria is phagocytosis. Cells capable of phagocytosing macrophages in natural responses play a role in presenting antigens to lymphocytes in specific immune responses. The number of lymphocytes associated with the incidence of death in TB patients in hospitals. This study aims to determine the lymphocyte profile in pulmonary TB patients with new cases in the city of Semarang in 2020. This study uses a descriptive-analytic research design. The population in this study were new cases of pulmonary TB patients at the Semarang Health Center in 2020. The sample in this study was new cases of pulmonary TB patients at the Semarang Health Center from September to October 2020. The results showed that the newest cases of pulmonary TB were male (59%), and based on age the most were productive age (87.8%), and the lymphocyte profile of 78% of respondents had relative lymphopenia, 19.5% of respondents were normal and 2.4% of respondents experienced relative lymphocytosis. Overall, it can be said that the profile of patients with lymphopenia is 14.63%, and relative lymphopenia is 78%.